APLIKASI PEMBANGKIT DATA BINER DAN HEXADESIMAL PADA DESAIN MOTIF TENUN - Sarmidi - (LPPM STMIK DCI, 2014)
addition, these motifs have a diversity that can not be separated from the background history and culture of Indonesia .Any element of tradition and customs often make motifs have meaning philosophy. As with the nut on the stem motif Minangkabau songket parable meaning noble human nature , which is straight and honest nature .Design and manufacture of fabrics that have a motif requires a process of very difficult if done using traditional weaving machine tools and manuals . In addition to requiring specific skills in using the manual loom , loom manuals were difficult to obtain.In the computer world we recognize four types of numbers , ie say binary , octal , decimal and hexadecimal . These four numbers were related to one another . Formula or how to find it quite easy to learn . Conversion from decimal to a non - decimal , just look for the rest of the division alone .Keyword : Weaving motif, Binary, Octal, Decimal, Hexadecimal.